[Kaplica Królewska] [aut. odb. Karol Nowaliński]. - Nowaliński, Karol (1935- ). (Karol Nowaliński, 1986)
Przedstawia Kaplicę Królewską, widok z ul. Świętego Ducha (Heilige-Geist-Gasse) od wschodu, ok. 1900 r.